Molecular analysis of a leprosy immunotherapeutic bacillus provides insights into Mycobacterium evolution. - Niyaz Ahmed (Public Library of Science (PLoS), 2007)
Background Evolutionary dynamics plays a central role in facilitating the mechanisms of species divergence among pathogenic and saprophytic mycobacteria. The ability of mycobacteria to colonize hosts, to proliferate and to cause diseases has evolved due to its predisposition to various evolutionary forces acting over a period of time. Mycobacterium indicus pranii (MIP), a taxonomically unknown 'generalist' mycobacterium, acts as an immunotherapeutic against leprosy and is approved for use as a vaccine against it. The large-scale field trials of this MIP based leprosy vaccine coupled with its demonstrated immunomodulatory and adjuvant property has led to human clinical evaluations of MIP in interventions against HIV-AIDS, psoriasis and bladder cancer. MIP, commercially available as 'Immuvac', is currently the focus of advanced phase III clinical trials for its antituberculosis efficacy. Thus a comprehensive analysis of MIP vis-à-vis evolutionary path, underpinning its immanent immunomodulating properties is of the highest desiderata. Principal findings Genome wide comparisons together with molecular phylogenetic analyses by fluorescent amplified fragment length polymorphism (FAFLP), enterobacterial repetitive intergenic consensus (ERIC) based genotyping and candidate orthologues sequencing revealed that MIP has been the predecessor of highly pathogenic Mycobacterium avium intracellulare complex (MAIC) that did not resort to parasitic adaptation by reductional gene evolution and therefore, preferred a free living life-style. Further analysis suggested a shared aquatic phase of MAIC bacilli with the early pathogenic forms of Mycobacterium, well before the latter diverged as 'specialists'. Conclusions/significance This evolutionary paradigm possibly affirms to marshall our understanding about the acquisition and optimization of virulence in mycobacteria and determinants of boundaries therein.